Biodiesel from waste cooking oil: sodium carbonate modified sand as filter, TLC and the unmodified domestic microwave oven approach - Barbosa, Sandro Luiz; Miranda, Savio Eduardo Oliveira; Barbosa, Bruna Kaicy; Ottone, Myrlene; klein, Stanlei Ivair; Baroni, Adriano Cesar Morais; Hurtado, Gabriela Ramos (Eclética Química, 2016)
Biodiesel is obtained by transesterification of animal and vegetable triglycerides (fats), and have several advantages over fossil fuel, perhaps the most important being its renewable source and its lack of pollutants such as aromatic and sulfur components. However, biodiesel from vegetable sources such as Soya beans is expensive, and it raises the question of planting for combustibles not for food. The most interesting alternative source for biodiesel is the non expensive waste cooking oil, WCO, which also brings the obvious benefit of transforming a severe pollutant into a green combustible. WCO consists of the triglycerides, but also contains left over food solids, which must be removed by filtration, mono and diglycerides, which are the source of the WCO free fatty acids (FFA), which must be converted to esters before the transesterification of the triglycerides, or, as usually reported, saponification of the final biodiesel mixture will occur.